UPAH MINIMUM DAN TINGKAT KEMISKINAN: STUDI KEBIJAKAN DI INDONESIA - Amir Husni, A. Hasyim Asyari; Rusli, A.M; Syamsu, Suhardiman; Ansar, Muhammad Chaeroel (Jurnal Administrasi Negara, 2023)
This study aims to investigate the relationship between minimum wages and poverty rates. Minimum wage is a controversial policy topic that affects millions of workers around the world, and understanding its impact on poverty rates is crucial for policymakers and researchers. By conducting a comprehensive analysis of existing literature, statistical data, and using more complex regression models. The data was processed in Microsoft Excell, and then analysed using R statistical software. The findings of this study show that minimum wage policy is effective in negatively affecting the poverty rate in Indonesia.